How the city works - Hobson, Oscar (London : News Chronicle Book Dept., 1959)
This book surveys the present organisation and working of the institutions which are the core of the City-the banking system, the foreign exchange and bullion markets, the Stock Exchange and the commodity markets. There are also chapters on Treasury Bills, Monetary Control and Exchange Control. In this edition the author revised the whole text, he also added chapters on two other important financial institutions, namely, Building Societies and Hire Purchase Finance Houses, which if not geographically located in the city, are functionally part of it. The book is very sound and easy to read, giving the reader a sense of having been taken close to the institutions which it describes.
Includes index.
rpm 23/04/2018
Loans
Keywords: Finance; Banks and banking; London (England)